Determination of antioxidant capacity of medicinal tinctures using cuprac method involving Cu(II) neocuproine immobilized into polymethacrylate matrix; Spectrochimica Acta Part A: Molecular and Biomolecular Spectroscopy; Vol. 240 - Saranchina N. V. Nadezhda Vasilievna; Damzina A. A. Anna Aleksandrovna; Ermolaev Ya. E. Yarovslav Evgenjevich; Urazov E. V. Eldar Valentinovich; Gavrilenko N. A. Natalia Airatovna; Gavrilenko M. A. Mikhail Alekseevich (2020, 2020)
Title screen